الوصية الواجبة من خلال الاجتهاد الفقهي المعاصر والقانون الجزائري - حايد, فريدة (جامعة الوادي university of eloued, 2022)
ملخص الوصية عمل خيري دون مقابل يقدم عليه الإنسان آخر حياته لمساعدة المحتاجين والأقارب غير الوارثين حماية لهم من الفقر بعده، وقد يحدث أن يتوفى الابن قبل الأب ويترك أولادا؛ فالقواعد العامة للميراث تقتضي حجبهم منه، أما قواعد الشريعة العامة فتقتضي تقديمهم عن الميراث بنصيب يعتبر صدقة ومعروفا حماية لهم يسمى الوصية الواجبة؛ وهذا ما ألزمت به القوانين العربية نظرا لفساد الذمم وتراجع الأخلاق والتكافل الأسري والاجتماعي في ضوء اجتهاد فقهي معاصر جمع بين أدلة الشرع واجتهادات جميع المذاهب مثبتين قدرة الشريعة على الإحاطة بحوادث الناس وإيجاد الحلول لقضاياهم المستجدة. : A will is generally considered a charitable act; A person offers her the last of his life for To help the needy and relatives who do not inherit; This is to protect them from need and poverty after him, and it may happen that the son dies before the father and leaves children; The general rules of inheritance decide to prevent them from inheriting by their uncles, As for the general rules of Sharia law, it is decided that their share is provided for the inheritance, and it is considered a charity to protect them, called the Obligatory Will; This is what Arab laws were obligated In light of contemporary jurisprudential jurisprudence, which combined Evidence of Islamic law and the jurisprudence of all schools of thought, and by this they proved the ability of Islamic law to find solutions to new people's accidents
مقال
Keywords: الوصية الواجبة، الاجتهاد الفقهي، التنزيل، القانون الجزائري; obligatory will, jurisprudential jurisprudence, download